2011
DOI: 10.21236/ada552439
|View full text |Cite
|
Sign up to set email alerts
|

Tailored Training in Army Courses

Abstract: The research aimed to identify different ways Army course instructors adapt or tailor their training to meet student needs. Interviews with 81 instructors from 51 courses across four installations were conducted. No single template existed regarding how instructors tailored, and some typical modes of tailoring were not described. Instructors provided details of how their courses were conducted as well as impediments to tailoring training. Characteristics of the courses and the instructors that increased the li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2012
2012
2014
2014

Publication Types

Select...
4
2

Relationship

5
1

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 15 publications
0
16
0
Order By: Relevance
“…To answer the second question, we interviewed U.S. Army course instructors and managers to determine what methods of adaptation are in current use (Dyer, Wampler, & Blankenbeckler, 2011). We describe the specific course selection methods and present the adaptive training approaches described by the instructors.…”
mentioning
confidence: 99%
“…To answer the second question, we interviewed U.S. Army course instructors and managers to determine what methods of adaptation are in current use (Dyer, Wampler, & Blankenbeckler, 2011). We describe the specific course selection methods and present the adaptive training approaches described by the instructors.…”
mentioning
confidence: 99%
“…It is acknowledged that the prior knowledge correlations were not always high, but they were consistent. We knew from prior research (Dyer, Wampler, & Blankenbeckler, 2011) that instructors did not frequently use formal or systematic techniques to identify students with minimal knowledge or those with much prior knowledge. They would informally query some students about their military experience in order to identify those who might excel in the course and those who would have difficulty.…”
Section: Lessons Learned From the Ari Research On Predicting Performamentioning
confidence: 99%
“…Recent research has indicated that a number of courses are already applying tailored training to address individual or small group student needs. Even so, many other courses-even those that exhibit some ALM learner-centric characteristics-seemed to remain centered on trainers and institutions, rather than on students (Dyer, Wampler, & Blankenbeckler, 2011).…”
Section: Impact Of Imi Within the Context Of The Almmentioning
confidence: 99%
“…A major consideration when examining the existing IMI was to determine what would be required to incorporate various tailoring principles to address the point of need with an eye toward future development of IMI. Dyer, Wampler, and Blankenbeckler (2011) identified forms of tailored training, provided examples of tailored training in Army courses, and even offered explanations why selected forms of tailoring might be more applicable to Army training. In our research, we considered a mix of approaches to tailoring IMI.…”
Section: Adapting Imi To Point Of Needmentioning
confidence: 99%